Advertising and social responsibility in Swedish alcohol advertising - Johansson, Elisabeth; Pettersson, Claudine (2005)
As Sweden quite recently allowed alcohol advertising we thought that it could be an interesting area to study. Therefore, the purpose of this study is to provide a better understanding on the social responsibility of Swedish alcohol advertising. This purpose is reached through two research questions, focusing on how the elements of advertising messages can be described, and how the tools used can be described. The study has a qualitative approach and data was collection through one focus group interview with students from Luleå University of Technology. The findings of this study indicate that colors can give all sorts of different associations, depending on the perception and preferences of the person. Warnings labels are good to have, even though people do not care about them, and a slogan as well as a warning label should be included when advertising controversial products like alcohol. Furthermore, our conclusions suggest that warnings labels should exist, but a change of the text is necessary. Advertisers need to take their social responsibility and not advertise in magazines which target underage readers. Television commercials should include a warning at the end. Finally, the Internet is a great way of getting information, but not the best way to advertise and certainly not the best way to be socially responsible, as many Internet users are underage. Validerat; 20101217 (root)